2016
DOI: 10.1111/bju.13715
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification: a tool to predict the course of active surveillance for localized prostate cancer?

Abstract: Our results show no differences in the outcome of risk-stratified patients in the specified risk groups managed with AS, while switching to an invasive treatment on the patient's request was more frequent in the intermediate-/high-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…2c). In this context, we were able to demonstrate in a previous investigation of our cohort, that the main reason for intervention in the intermediate-/high-risk group was patient preference without sings of progression [22].…”
Section: Discussionsupporting
confidence: 53%
“…2c). In this context, we were able to demonstrate in a previous investigation of our cohort, that the main reason for intervention in the intermediate-/high-risk group was patient preference without sings of progression [22].…”
Section: Discussionsupporting
confidence: 53%
“…Carlsson et al [18] found that nearly 30% of definitive treatment was related to patients' preference. Similarly, whereas in the LR group, most patients received deferred treatment due to tumor progression, patients with IR mainly discontinued AS at their own convenience in the study by Herden et al [23]. On the one hand, these results indicate that patients/physicians may have a greater fear of tumor progression.…”
Section: Discussionmentioning
confidence: 96%
“…Many cohorts have included men with intermediate-risk under AS [ 14 , 24 , 25 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Table 2 shows a summary of studies including intermediate-risk patients undergoing AS and compares oncological outcomes between low-risk and intermediate-risk.…”
Section: Criteria For Inclusion Monitoring and Trigger For Interventionmentioning
confidence: 99%